My Pilgrimage in Mission - Ma, Wonsuk (International bulletin of mission research, 2016)
This self-reflection on my missionary journey is characterized as a process of learning, particularly about the meaning of mission. Missionary formation is part of one's spiritual development, and for me, immersion in several cross-cultural contexts accelerated the process. Through long years in the Philippines, combined with study in the United States, my understanding of mission deepened. Another decade of mission leadership at OCMS in Oxford added further dimensions of my understanding of mission. Through this continuing journey, I have had several surprise teachers of mission. Reflecting experiences in a new missionary church, this pilgrimage may speak for mission workers of the Global South.